2014
DOI: 10.1007/s11095-014-1352-0
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-Dipole Interaction in Antibody Solutions: Correlation with Viscosity Behavior at High Concentration

Abstract: The solution pH dependent measured dipole moments of MAb1 appears to be in line with the observed intermolecular interactions and viscosity behavior suggesting that dipole-dipole interaction plays an important role in governing the high concentration solution behavior of this MAb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…Besides net charge, the distribution of charge across the molecule can influence the solution behavior of a protein. Strong asymmetric charge distribution was shown to be correlated to a tendency of such molecules to self‐interact, potentially leading to high‐viscosity or high‐aggregation tendency . In summary, calculation of pI, net charge, and charge distribution can guide molecule selection and/or engineering, whereas the detailed mechanisms leading, for example, to high viscosity, still remain complex and challenging to predict.…”
Section: Desired Molecular Features and Test Methods Used During Devementioning
confidence: 99%
“…Besides net charge, the distribution of charge across the molecule can influence the solution behavior of a protein. Strong asymmetric charge distribution was shown to be correlated to a tendency of such molecules to self‐interact, potentially leading to high‐viscosity or high‐aggregation tendency . In summary, calculation of pI, net charge, and charge distribution can guide molecule selection and/or engineering, whereas the detailed mechanisms leading, for example, to high viscosity, still remain complex and challenging to predict.…”
Section: Desired Molecular Features and Test Methods Used During Devementioning
confidence: 99%
“…As previously reported, the high viscosity of some types of antibodies can be attributed to reversible self-association induced by heterogeneous charge distribution on the protein surface and the accompanying electrostatic attraction (e.g., dipole-dipole interaction) (2)(3)(4)(5) demonstrated by using dielectric relaxation spectroscopy that the pH dependence of viscosity of some types of antibody is synchronized with that of the dipole moment, suggesting that dipole-dipole interaction plays an important role in governing the viscosity behavior of the antibody at high concentration (12). In addition, some antibodies with high viscosity have been reported to exhibit liquid-liquid phase separation or opalescence at low salt concentrations in accordance with the fact that electrostatic attraction is enhanced by decreased salt concentrations (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for some mAbs it has been shown that "hydrophobic" salts can disrupt interactions resulting in viscosity decrease (Du & Klibanov, 2011), whereas addition of ionic salts can decrease viscosity for other mAbs (Kanai et al, 2008;Liu et al, 2005). In the case of several mAbs it has been shown that the main attractive interactions are electrostatic in nature and that measured average dipole moments for mAb1 and mAb2 as a function of pH correlate with the DLS interaction parameter, k D and G′ and viscosity measurements (Figure 9.10) (Singh, Yadav, Shire, & Kalonia, 2014). In particular, the magnitude of the mAb1 dipole moment increased from pH 4 to 6.5 and fell off sharply from pH 7 to 9.0, whereas the dipole moment for mAb2 with the same IgG 1 human Fc framework as mAb1 has its largest magnitude somewhere between pH 7 to 9, and is significantly lower at pH 6.5.…”
Section: Aggregation and Viscosity Of Mabsmentioning
confidence: 93%